Privacy, Ethics, And Security On Social Media: An Islamic Overview - Karyono, Giat; Ahmad, Asmala; Asmai, Siti Azirah (World Academy of Research in Science and Engineering, 2019)
Privacy is one of the most critical fields in recent years since the presence of social media that is increasingly eroding the fundamental human right to privacy. This phenomenon raises many people's concerns about the future o privacy. Commonly discussed by many people are privacy, ethics, and security, including the extent to which they are being taken seriously by designers and users social media. The discussion is not only from the perspective of western culture but also from the religious point of view. The purposes ot this paper is to investigate the privacy, ethics, and security concerns in social media from an Islamic overview. Towards this, we begin by introducing the Qur'an and Sunnah as the life guidelines for humanity. We then highlight the mention of privacy, ethics, and security in both these guidelines. Then we explain it in sequence in each section accompanied by the existing problems in social media. Finally, we discuss the future of privacy in social media.